The Capital Purchase Program and subsequent bank SEOs - Khan, Mozaffar; Vyas, Dushyantkumar (Journal of Financial Stability, 2015)
We find that in the aftermath of the recent financial crisis banks replenished only 12% of crisis-related losses through SEOs in 2009 and 2010. However, SEOs are disproportionately conducted by Capital Purchase Program (CPP) recipients, and this is not explained by CPP recipients’ economic and regulatory capital needs. SEOs in 2009 and 2010 by CPP recipients alone account for 27% by number, and 50% by dollar amount, of all SEOs by U.S. banks between 1994 and 2010, indicating the CPP is an influential event in the history of U.S. bank SEOs during this period. Controlling for economic and regulatory capital determinants of SEOs, CPP recipients were more likely than non-recipients to have a SEO within four quarters subsequent to CPP receipt. SEO proceeds were used to repay CPP receipts without jeopardizing loan growth. Banks that received CPP funds prior to the passage of the American Recovery and Reinvestment Act (ARRA), and banks with greater reliance on non-traditional banking activities, were more likely to have a SEO expeditiously and repay CPP funds early. Collectively, the results provide new evidence on the realized consequences of the CPP for bank SEOs. Tests suggest the CPP's indirect costs of restrictions on corporate policies and actions as the most likely explanation for the results.